Quality assessment, sensory evaluation, and radical scavenging activity (RSA) of orange (Citrus auranthium) pulp - Saeed, MK; Zahra, N; Ahmad, I; Syed, Q (Bangladesh Journal of Scientific and Industrial Research, 2022)
Oxidative stress is a significant source of the pathogenesis of many chronic diseases; that is why antioxidant behavior is one of the most commonly identified biological activities in citrus fruits. The pulp of citrus fruits is the sticky substance of the fruit's endocarp and contains the fruit's juice. This study scrutinizes the quality assessment, sensory evaluation, and free radical scavenging activity (RSA) of orange (Citrus auranthium) pulp. Free radical scavenging activity was examined by 2, 2-diphenyl-1-picrylhydrazyl assay. The quality assessment parameters results showed that the ºBrix of orange pulp was 64.50, pH 3.70, acidity 5.12, ratio 12.58, pulp 9.70%, and SO2 were not detected. On analyzing the sensory evaluation, it was found that orange pulp juice has the score of appearance (7.07 ± 0.146), color (7.27 ± 0.163), flavor (7.52 ± 0.172), taste (6.87 ± 0.156), and overall acceptability (7.60 ± 0.165). The results of free radical scavenging showed that the percentage inhibition was 9.55-54.80 at concentrations of 0.2-1.0 mg/ml. The antioxidant activity of orange pulp may be due to presence of polyphenols, flavonoids and possibly other compounds in orange pulp that are responsible for this activity. Bangladesh J. Sci. Ind. Res. 57(2), 123-130, 2022